Topological Optimization of the Femoral Stem: A Comparative Study between Titanium Ti-6Al-4V and Cobalt-Chromium Alloy - Serna-Landivar, José Luis; Risco Sernaque, Madelaine Violeta; Anticona-Valderrama, Daniela Milagros; Mendoza Damas, Marleni; Garcia-Alvarez, Maria Ysabel; Algoner, William C. (International Journal of Online and Biomedical Engineering (iJOE), 2026)
The present study evaluates the structural behavior of a topologically optimized femoral stem, comparing two metallic materials commonly used in orthopedics: Ti-6Al-4V titanium and cobalt-chrome alloy (CoCr). The three-dimensional model was developed in SolidWorks and analyzed using finite element simulations in ANSYS, following the guidelines of ASTM F2996-20. Six optimized configurations were defined by varying the percentage of retained mass (25%, 35%, and 45%) for each material, assessing displacements, von Mises stresses, and mass reduction. The results show that the configurations with higher retained mass (J1 and J5) exhibited less deformation and more uniformly distributed stresses, remaining within the elastic regime. The optimized design in Ti-6Al-4V with 25% retained mass stood out, achieving a 27.9% weight reduction with high structural safety factors. This study confirms that topological optimization, when applied to clinically approved metallic materials, enables the development of orthopedic implants that are stronger, lighter, and mechanically compatible, contributing to sustainable surgical solutions.